Menantang Tembok Patriarki: Aktivis Perempuan LRC KJHAM dan Upaya Advokasi Kasus KDRT di Kota Semarang - Alya Meuthia Zahwa; Wida Ayu Puspitosari (Brawijaya Journal of Social Science, 2022)
Domestic violence is one among common violence in Indonesia. It has been a critical problem that women activists are striving for solutions. However, in finding ways out of this problem, they frequently face challenges, both structurally and culturally, which also affect some who devote their efforts at the Legal Resources Center for Gender Justice and Human Rights (LRC KJHAM). Challenges at the structural and cultural levels eventually became serious obstacles to fight for rights and justice for the victims, as well as promoting gender in Semarang. This article discusses the structural and cultural obstacles of one of the women's activist groups in Semarang, namely the women activists at the Legal Resources Center for Gender Justice and Human Rights (LRC KJHAM).